La crise alimentaire, le développement durable et les biocarburants : perspectives d’avenir - Erwan Cheneval; Ariane Adam-Poupart; Joseph Zayed (VertigO)
Biofuels, extracted from cereals and other food crops, are attracting greater interest, especially as a substitute for fossil energy. However, the use of food products for biofuel production has been recently described as crime against humanity, since it contributes to raise the world market food prices and intensifying the world hunger. To assess the effect of the biofuels market on the global food crisis, an analysis based on key dimensions of sustainable development (economic, social and environmental) was performed. Economically, biofuels compete with food, which causes an increase in food prices. In social terms, this energy may increase food insecurity and malnutrition via decreased availability of food for consumption, but also because of the significant amount of water used for irrigation of crops. On the environmental front, the market for biofuels will affect the quality of ecosystems through the depletion of water resources, soil pollution by fertilizers and loss of biodiversity. Biofuels made from raw materials other than food products are currently being studied and appear to offer promising solutions. It is advisable to conduct an environmental and social impacts assessment before massive exploitation, in order to avoid side effects, such as those created by the first generation of biofuels.